Marketing Strategies of Companies in Internationalization Process - SPIVAKOVSKYY, Sergiy; SPIVAKOVSKA, Tetiana; KANISHCHENKO, Olena; ELALFY, Shahira (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
The article concerns the options of company internationalization, depending on the degree of market internationalization. The main indicators for assessing the degree of company internationalization were determined. The specificity of companies’ internationalization in terms of the concept of international product life cycle was analyzed. The features of international marketing strategy in the internationalization process were examined; the determinants of international marketing strategy were described. The relationship between the phases of international marketing and the level of application of international marketing strategy was determined. The level of application of international marketing strategy by Ukrainian enterprises was researched.